Importance of the Amino Acid Transporter SNAT1/SLC38A1 in malignant Melanoma - Lörentz, Sandra; Böhme-Schäfer, Ines; Boßerhoff, Anja Katrin (JOURNAL DER DEUTSCHEN DERMATOLOGISCHEN GESELLSCHAFT, 2022)
CRIS-Team WoS Importer:2022-09-23

NPT100-18A rescues mitochondrial oxidative stress and neuronal degeneration in human iPSC-based Parkinson's model. - Alecu, Julian; Sigutova, Veronika; Brazdis, Razvan Marius; Lörentz, Sandra; Marios-Evangelos, Bogiongko; Nursaitova, Anara; Regensburger, Martin; Roybon, Laurent; Galler, Kerstin Martina; Wrasidlo, Wolfgang; Winner, Beate; Prots, Iryna (BMC Neuroscience, 2025)
BACKGROUND: Parkinson's disease (PD) is a neurodegenerative disorder characterized by protein aggregates mostly consisting of misfolded alpha-synuclein (αSyn). Progressive degeneration of midbrain dopaminergic neurons (mDANs) and nigrostriatal projections results in severe motor symptoms. While the preferential loss of mDANs has not been fully understood yet, the cell type-specific vulnerability has been linked to a unique intracellular milieu, influenced by dopamine metabolism, high demand for mitochondrial activity, and increased level of oxidative stress (OS). These factors have been shown to adversely impact αSyn aggregation. Reciprocally, αSyn aggregates, in particular oligomers, can impair mitochondrial functions and exacerbate OS. Recent drug-discovery studies have identified a series of small molecules, including NPT100-18A, which reduce αSyn oligomerization by preventing misfolding and dimerization. NPT100-18A and structurally similar compounds (such as NPT200-11/UCB0599, currently being assessed in clinical studies) point towards a promising new approach for disease-modification. METHODS: Induced pluripotent stem cell (iPSC)-derived mDANs from PD patients with a monoallelic SNCA locus duplication and unaffected controls were treated with NPT100-18A. αSyn aggregation was evaluated biochemically and reactive oxygen species (ROS) levels were assessed in living mDANs using fluorescent dyes. Adenosine triphosphate (ATP) levels were measured using a luminescence-based assay, and neuronal cell death was evaluated by immunocytochemistry. RESULTS: Compared to controls, patient-derived mDANs exhibited higher cytoplasmic and mitochondrial ROS probe levels, reduced ATP-related signals, and increased activation of caspase-3, reflecting early neuronal cell death. NPT100-18A-treatment rescued cleaved caspase-3 levels to control levels and, importantly, attenuated mitochondrial oxidative stress probe levels in a compartment-specific manner and, at higher concentrations, increased ATP signals. CONCLUSIONS: Our findings demonstrate that NPT100-18A limits neuronal degeneration in a human in vitro model of PD. In addition, we provide first mechanistic insights into how a compartment-specific antioxidant effect in mitochondria might contribute to the neuroprotective effects of NPT100-18A.
EVALuna2:586322
Keywords: iPSC; Dopaminergic neurons; Alpha-synuclein; Aggregation; Parkinson’s disease; Oxidative stress; NPT100-18A; Mitochondria; ROS

Role of Amino Acid Transporter SNAT1/SLC38A1 in Human Melanoma - Böhme-Schäfer, Ines; Lörentz, Sandra; Boßerhoff, Anja Katrin (Cancers, 2022)
The tumor metabolism is an important driver of cancer cell survival and growth, as rapidly dividing tumor cells exhibit a high demand for energetic sources and must adapt to microenviron-mental changes. Therefore, metabolic reprogramming of cancer cells and the associated deregulation of nutrient transporters are a hallmark of cancer cells. Amino acids are essential for cancer cells to synthesize the necessary amount of protein, DNA, and RNA. Although cancer cells can synthesize glutamine de novo, most cancer cells show an increased uptake of glutamine from the tumor microen-vironment. Especially SNAT1/SLC38A1, a member of the sodium neutral amino acid transporter (SNAT) family, plays an essential role during major net import of glutamine. In this study, we revealed a significant upregulation of SNAT1 expression in human melanoma tissue in comparison to healthy epidermis and an increased SNAT1 expression level in human melanoma cell lines when compared to normal human melanocytes (NHEMs). We demonstrated that functional inhibition of SNAT1 with α-(methylamino) isobutyric acid (MeAIB), as well as siRNA-mediated downregulation reduces cancer cell growth, cellular migration, invasion, and leads to induction of senescence in melanoma cells. Consequently, these results demonstrate that the amino acid transporter SNAT1 is essential for cancer growth, and indicates a potential target for cancer chemotherapy.
CRIS-Team Scopus Importer:2022-05-06
Keywords: amino acid transporter; melanoma; tumor metabolism